2016
DOI: 10.1186/s13148-016-0281-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of prenatal DHA supplementation on the infant epigenome: results from a randomized controlled trial

Abstract: BackgroundEvidence is accumulating that nutritional exposures in utero can influence health outcomes in later life. Animal studies and human epidemiological studies have implicated epigenetic modifications as playing a key role in this process, but there are limited data from large well-controlled human intervention trials.This study utilized a large double-blind randomized placebo-controlled trial to test whether a defined nutritional exposure in utero, in this case docosahexaenoic acid (DHA), could alter the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(45 citation statements)
references
References 58 publications
1
43
1
Order By: Relevance
“…The level of omega-3 fatty acids in the mother's bloodstream during pregnancy has been shown to correlate with insulin levels [46] and adiposity [47]. Newer lines of inquiry have indicated that prenatal DHA during the second half of pregnancy alters the infant epigenome (gene activity changes that do not affect the DNA sequence) and can alter developmental programming [48].…”
Section: Omega-3 Fatty Acidsmentioning
confidence: 99%
“…The level of omega-3 fatty acids in the mother's bloodstream during pregnancy has been shown to correlate with insulin levels [46] and adiposity [47]. Newer lines of inquiry have indicated that prenatal DHA during the second half of pregnancy alters the infant epigenome (gene activity changes that do not affect the DNA sequence) and can alter developmental programming [48].…”
Section: Omega-3 Fatty Acidsmentioning
confidence: 99%
“…A recent randomized controlled trial providing the omega-3 polyunsaturated fatty acid (n-3 PUFA) DHA to pregnant women reported differences in methylation in some DNA regions in their children relative to a control group [38].…”
Section: Nutrient Supply and Early Programmingmentioning
confidence: 99%
“…BMI, body mass index. epigenetic mechanism, it was reported that maternal omega-3 PUFA induced changing of methylation level in differentially methylated regions [12] and the promoter methylation level of Interferon γ and IL13 [62]. Maternal omega-3 PUFAs regulated offspring obesity through recomposition of the gut microbiota, Epsilonproteobacteria, Bacteroides, Akkermansia, and Clostridia [63].…”
Section: Maternal Nutrients Influence On Microbiome and Epigenetic Momentioning
confidence: 99%
“…Non-coding RNA is an epigenetic mark that mediates epigenetic modification by environmental factors such as diet. Modification of chromatin architecture by epigenetic marks can be heritable and modify the risks of disease in later life (Table 1) [7][8][9][10][11][12][13][14][15][16][17].…”
Section: The Link Between Dietary Epigenetic Modulator and Metabolic mentioning
confidence: 99%